Public knowledge of emergency medicine in Beirut, Lebanon - Mufarrij, Afif (BMC Emerg Med, 2018)
INTRODUCTION: To examine the public’s level of knowledge and expectations of Emergency Medicine (EM) in Beirut, Lebanon. METHODS: A nested cross-sectional study was conducted exploring participants’ knowledge and expectations of EM; the skillset, role and scope of practice of the emergency physician, and the dynamics of the Emergency Department (ED). RESULTS: A majority understand EM physicians perform minor procedures (83%), have specialized training (79%) and that they should be treated by a specialized EM physician (74%). However, they also believed they should visit the ED for faster service (81%) or whenever they cannot be seen by their doctor (71%); most also expected to see their personal doctors in the ED (88%). There were significant misconceptions that ED physician could be a general doctor (84%), a specialist (81%) or a family doctor (70%). Half believe patients have the right to order blood tests (46%) or X-rays (50%) and to be admitted to the hospital at their preference (51%). Most (90%) expected patients with a possibly life-threatening problem to be treated immediately, and 48% a wait of less than thirty minutes for a non-life threatening problem. Half (54%) expected test results returned within thirty minutes, and 62% expected to spend less than sixty minutes in the ED. CONCLUSION: There is poor recognition of the role of the EM physician and the dynamics of the ED among the Lebanese population. Awareness campaigns targeted to improve understanding may help align expectations with the reality of the practice of EM.